Sociology in modules - Schaefer, Richard T. (McGraw-Hill, 2013)
Make Sociology new with McGraw-Hill’s Connect Sociology and the 2nd edition of Sociology in Modules. New to Connect is Investigate Sociology, a brand-new tool that develops students’ sociological imaginations by placing them in provocative scenarios where they must analyze various sources and determine a solution. Connect also comes with LearnSmart, an adaptive questioning tool proven to increase content comprehension and student results, as well as fun interactivities like In their Shoes and Applying the Perspectives that teach sociology’s three theoretical frameworks